Mechanochemical Asymmetric Transfer Hydrogenation of Diketones to Access Chiral 1,3-Diols under Solvent-Free Conditions - Wang, Chengyi; Deng, Shaomin; Chen, Rui; Liu, Guohua; Cheng, Tanyu; Liu, Rui (Synlett, 2022)
A mechanochemical asymmetric transfer hydrogenation (ATH) of diketones in the presence of a ruthenium complex under solvent-free conditions was developed to provide chiral 1,3-diol derivatives. This protocol benefits from rapid reaction kinetics, no use of solvents, and excellent enantioselectivity. In addition, the mechanochemical ATH reaction can easily be performed on a gram scale.
Keywords: asymmetric catalysis; transfer hydrogenation; mechanochemistry; diols; ruthenium catalysis; solvent-free reaction